Pengaruh Motivasi Kerja, Pelatihan dan Kompensasi Finansial terhadap Kinerja Karyawan PT. Bank Kalsel Cabang Martapura - Januar Pujiasymi; Hairudinor Hairudinor; Taharuddin Taharuddin (Universitas Lambung Mangkurat, 2017)
The purpose of this study to prove the effect of. Work motivation (X1), Training (X2) and Financial Compensation (X3) to the Employee Performance (Y).The study populaton was all employees of PT. Bank Kalsel, Martapura branches totaling 40 people. Sampling technique used sampling saturated. Collecting data using questionnaires designed using level Likert scale 1-5. Data analysis using the structural model SmartPLS.The test results prove 1). Work Motivation signifikan` affect the Employee Performance PT Bank Kalsel employees with major influence (33.11%) 2). Training significantly influence employee performance PT Bank Kalsel with great influence of 24.34% 3) Financial Compensation significant influence significantly the Employee Performance PT Bank Kalsel with great influence of 31.11%. Keywords: Work Motivation, Training, Financial Compensation and Employee Performancee